Penggunaan Bibliotherapy dalam Membantu Penyesuaian Diri pada Mualaf Tionghoa Masjid Al-Islam Muhammad Cheng Ho Palembang - Neny Noviza (Pusat Penelitian dan Penerbitan Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Negeri Raden Fatah Palembang, 2015)
This paper is the result of research that reviewing the background of Chinese converts perform religious conversion to Islam, by taking three samples of the subjects on Chinese converts in Masjid Al-Islam Muhammad Cheng Ho. Factors that causing religious conversion on the first and second subject is the influence of interpersonal relationships and the influence of the advice from those closest. Meanwhile, the third subject motivated by self exemption from inner pressure and external factors that influence like loneliness and lack of recognition of the relatives of nearby people. These three subjects experienced all phases of religious conversion among the quiet period, disquiet period, the conversion period, a quiet and peaceful period, and a conversion expression. Environment is the strongest factor that drives the subjects perform religious conversion period. The subjects source to learn about the new religion are from friends, books, and religious leaders in Masjid Al-Islam Muhammad Cheng Ho. All subjects is a kind of volitional type (gradual change). The obtacles that faced is the adaptation to the new religion about how to do worship and to the family and work environment. When the subjects become a part of Al-Islam mosque Muhammad Cheng Ho, all the subjects find it easy to solve these problems, more curiosity about Islam, and get peace of mind.